Localized transverse flow measurement with dynamic light scattering line-scan OCT - Han, Le (2023)
A novel decorrelation-based approach for measuring localized transverse flow velocity using line-scan (LS) optical coherence tomography (OCT) is proposed. The new approach allows for separation of the flow velocity component along the line-illumination direction of the imaging beam from other orthogonal velocity components, from particle diffusion motion, and from noise-induced distortion in the OCT signal's temporal autocorrelation. The new method was verified by imaging flow in a glass capillary and a microfluidic device and mapping the spatial distribution of the flow velocity within the beam's illumination plane. This method can be extended in the future to map the three-dimensional flow velocity fields for both ex-vivo and in-vivo applications.